PENINGKATAN PERAN IBU RUMAH TANGGA MELAWAN ASAP ROKOK DALAM RUMAH MELALUI EDUKASI INTERAKTIF DAN PERMAINAN - Permana, Lies; Ifroh, Riza Hayati; Yuniar, Dewi (Jurnal Pengabdian Masyarakat Sasambo, 2025)
Smoking activities in the house are still common among families in Indonesia. This behavior can reduce the quality of family members' health, and the smoke produced from smoking activities for a while can affect the quality of the physical environment in the house. The low knowledge of family members regarding the dangers of cigarette smoke is one of the factors causing delays in efforts to reduce exposure to cigarette smoke at the household level. Housewives have an important role in fighting indoor cigarette smoke. This activity aims to increase the role of mothers in fighting cigarette smoke, especially by increasing knowledge about the dangers of cigarette smoke and effective communication with the family.Â Â The methods of implementing activities, include: 1) planning stages through community surveys to get an overview of the problem, 2) preparation with community leaders in preparing educational agendas and games, 3) implementation of activities by using power point media and flipcharts, and ranking 1 game which is used as the pretest process, and the final stage is, 4) evaluation of results by looking at the results of the pretest and posttest as well as process evaluation. The results of the activity obtained were an increase in the mother's knowledge regarding the dangers of cigarette smoke at home with an increase in the average pretest and posttest scores of the participants. The aspect of increased knowledge is that cigarette smoke cannot be described quickly in the house, because cigarette particles will stick to the surfaces of objects in the house for 4-6 hours. The limitations of the activity, there were a few technical obstacles to educational facilities and the psychological unpreparedness of some participants which were resulting in a lack of focus in discussion. Further research on the impact of smoking in the home still needs to determine the quality of health at the family level, and educational interventions based on behavior change are also needed for the primary target (active smokers) to create a smoke-free home at community level.